Best Practices in North American Pre-Clinical Medical Education in Sexual History Taking: Consensus From the Summits in Medical Education in Sexual Health. Issue 10 (1st October 2018) - Rubin, Elizabeth S.; Rullo, Jordan; Tsai, Perry; Criniti, Shannon; Elders, Joycelyn; Thielen, Jacqueline M.; Parish, Sharon J.
Abstract: Introduction: This article discusses a blueprint for a sexual health communication curriculum to facilitate undergraduate medical student acquisition of sexual history taking skills and includes recommendations for important elements of a thorough sexual history script for undergraduate medical students. Aim: To outline the fundamentals, objectives, content, timing, and teaching methods of a gold standard curriculum in sexual health communication. Methods: Consensus expert opinion was documented at the 2012, 2014, and 2016 Summits in Medical Education in Sexual Health. Additionally, the existing literature was reviewed regarding undergraduate medical education in sexual health. Main Outcome Measures: This article reports expert opinion and a review of the literature on the development of a sexual history taking curriculum. Results: First-year curricula should be focused on acquiring satisfactory basic sexual history taking skills, including both assessment of sexual risk via the 5 Ps (partners, practices, protection from sexually transmitted infections, past history of sexually transmitted infections, and prevention of pregnancy) as well as assessment of sexual wellness—described here as a sixth P (plus), which encompasses the assessment of trauma, violence, sexual satisfaction, sexual health concerns/problems, and support for gender identity and sexual orientation. Second-year curricula should be focused on incorporating improved clinical reasoning, emphasizing sexual history taking for diverse populations and practices, and including the impact of illness on sexual health. Teaching methods must include varied formats. Evaluation may be best as a formative objective structured clinical examination in the first year and summative in the second year. Barriers for curriculum development may be reduced by identifying faculty champions of sexual health/medicine. Clinical Implications: Medical students will improve their skills in sexual history taking, which will ultimately impact patient satisfaction and clinical outcomes. Future research is needed to validate this proposed curriculum and assess the impact on clinical skills. Strengths & Limitations: This article assimilates expert consensus and existing clinical guidelines to provide a novel structured approach to curriculum development in sexual health interviewing in the pre-clinical years. Conclusion: The blueprint for developing sexual history taking skills includes a spiral curriculum with varied teaching formats, incorporation of a sexual history script that incorporates inquiry about sexual wellness, and longitudinal assessment across the pre-clinical years. Ideally, sexual health communication content should be incorporated into existing clinical interviewing and physical examination courses.